Resolving individual labor disputes in Kazakhstan in the era of human rights (Journal of actual problems of jurisprudence, 2021)
The main role of labor law is that it harmonizes the interests of society, the state, as well as workers and employers in the field of employment. One of the mechanisms for ensuring such a reconciliation of interests is an effective judicial system, which must be “tuned” to the special subject composition of labor relations; should differentiate the principles of civil and labor contracts; to provide a special approach to the settlement of labor disputes, taking into account the vital necessity for citizens to participate in hired labor, to receive remuneration; take into account the risk for citizens of loss of life and health in labor relations if the employer does not comply with labor protection measures; take into account the impossibility of restoring the original position of the parties (bring the parties to their original position) when terminating the employment contract. The study is aimed at developing the theoretical and methodological foundations of the judicial form for resolving labor disputes. The scientific and practical significance of the work lies in the substantiation of proposals for further improving the procedures for resolving labor disputes. Methodologically, the study was carried out using traditional methods inherent in legal science: formal legal (dogmatic), sociological and legal, the method of legal modeling, as well as the critical legal method of legal knowledge. The main results are aimed at improving the current practice of implementing the judicial form of protecting social and labor human rights.Keywords: individual labor dispute, mediator, labor conflict, justice, labor law.